Sexual and reproductive practices of self-care in women partners of international migrants in San Luis Potosi, Mexico - Yesica Yolanda Rangel Flores (Universidad de Alicante, 2015)
Migrants and their partners have been incorporated into institutional discourses of health as "subjects at risk" against Sexually Transmitted Infections (STIs), however, the inclusion of this specific population in communication and risk management of STIs has been ambiguous in the Mexican context. The objective of this approach was explore sexual and reproductive practices of self-care they take in their everyday women "partner of migrant" and the relationship of these measures with communication and risk management conducted by health services. It was a qualitative approach with 20 women "partner of migrants" located by the health services, the information was gathered through in-depth interviews that focused on the areas of "risk perception" and "sexual and reproductive self-care". We found that most women do not recognize vulnerable to STIs and risk perception is not decisive in the confrontation about the threat to develop, the patriarchal imaginary prevailing in them, their partners and health workers rejecting the use of prevention and early detection.